Carrier transport and electron field-emission properties of a nonaligned carbon nanotube thick film mixed with conductive epoxy - Lee, YH; Kim, DH; Hoon-Kim; Ju, BK (AMER INST PHYSICS, 2000)
We have studied the conduction characteristics of multiwalled carbon nanotubes (MWNTs), which were screen printed in a thick film form for field-emission displays. Resistivity and magnetoresistance were measured as a function of temperature T in the range of 1.7-390 K and magnetic field, respectively. The resistivity of the MWNTs for temperatures of 10-390 K indicates that the system is intrinsically metallic and the resistivity-temperature characteristics are well described by the Mott's T-1/4 law in temperatures above 10 K, suggesting that the density of states at the Fermi level is constant in the range of 10-100 K. We found that the main contribution to the conductivity comes from carriers that hop directly between localized states via variable-range hopping. The temperature dependence above 10 K is in good agreement with that of an individual multiwalled carbon nanotube. However, below 10 K the resistivity is well fit to Efros T-1/2 law, confirming the presence of a Coulomb gap for the system. With the decrease of temperature below 10 K the charge carriers in the system are localized by strong disorder, bringing a nearly insulating state. The thick-film form for large-area display resulted in a highly bright light as well as a very low turn-on field just like individual multiwalled nanotubes at room temperature. Also, the electron field-emission characteristics followed typical Fowler-Nordheim conduction under high electric field. (C) 2000 American Institute of Physics. [S0021-8979(00)01117-8].
Keywords: POLYANILINE; EMITTERS